EFEKTIVITAS PENERAPAN SCIENTIFIC APPROACH TERHADAP HARD SKILL DAN SOFT SKILL SISWA PADA MATA PELAJARAN AL-QURAN HADITS KELAS VIII DI MTS PP.NURUL ISLAM KAMPUNG BARU KECAMATAN GUNUNG TOAR - Mici Asmiyum; Sarmidin Sarmidin; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Applying of scientific approach in course of study can make student have hard skill and soft skill, however still found problems concerning hard skill and soft skill student in schools and among others is MTS PP. Nurul Islam, that is : 1 ) At the time of to evaluate, student not yet can answer question truly 2) At the time of evaluation executed some of still student of disingenuous. This research aim to To know effectiveness of applying scientific approach towards hard skill and soft skill student at subject of Al-Quran Hadits Class VIII in MTs PPNI kampung baru of district gunung toar The research methodologhy qualitative where research descriptive qualitative.by using technique data collecting of observation, interview and dokumentas. as for technique analyse data that is discount data, presentation of data,and concluding and triangulasi. Effectiveness of applying scientific approach towards hard skill and soft skill student at subject of Al-Quran Hadits class VIII In MTs PPNI Kampung Baru Of District Gunung Toar got by result 83% so that can be concluded that Effectiveness of applying scientific approach towards hard skill and soft skill student at subject of Al-Quran Hadits class VIII In MTs PPNI Kampung Baru Of District Gunung Toar reside in at effective category, because residing in at spanning 61 - 85%. Kata Kunci : Efektivitas, Saintific Approach, Hard Skill, Soft Skill, Al-Quran Hadits